ALGORITHMS OF PROCESSING OF STEELS MICRO STRUCTURE IMAGES FOR DETERMINATION OF INTERPLATE DISTANCES OF FERRITE AND CEMENTITE - A. N. Chichko; O. N. Sachek; A. V. Vedeneev (Литьë и металлургия, 2009)
The methods of computer analysis, based on binarization of image for calculation of inter-plate distance in eutectic  colonies of pearlite steel are offered. Algorithms for determination of function of inter-plate distance, that allows to increase informativeness of microstructure investigations  and level of automation in determination of inter-plate distance, are developed.